2020
DOI: 10.2215/cjn.03630320
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak and Management Approach for Families with Children on Long-Term Kidney Replacement Therapy

Abstract: Background and objectivesDuring the coronavirus disease 2019 outbreak, the treatment of families with children on long-term KRT is challenging. This study was conducted to identify the current difficulties, worries regarding the next 2 months, and mental distress experienced by families with children on long-term KRT during the coronavirus disease 2019 outbreak and to deliver possible management approaches to ensure uninterrupted treatment for children on long-term KRT.Design, setting, participants, & meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Moreover, in our clinical practice, we have observed that some parents of pediatric transplant recipients have asked medical teams for documentation demonstrating their children’s health status in order to limit their own exposure in their work environment. This extra effort to protect themselves is probably due to their fear, in some cases, of working in the medical field in the COVID-19 context ( Menon et al, 2020 ) and, more specifically, to their fear of infecting their child, who they perceive as potentially more vulnerable than the general population ( Cousino et al, 2020 , Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in our clinical practice, we have observed that some parents of pediatric transplant recipients have asked medical teams for documentation demonstrating their children’s health status in order to limit their own exposure in their work environment. This extra effort to protect themselves is probably due to their fear, in some cases, of working in the medical field in the COVID-19 context ( Menon et al, 2020 ) and, more specifically, to their fear of infecting their child, who they perceive as potentially more vulnerable than the general population ( Cousino et al, 2020 , Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Zhao et al (2020) studied the effect of COVID-19 on families with children on dialysis and kidney transplantation. Almost 80% of the participants thought that COVID-19 negatively affected their child’s treatment, and a higher prevalence of depressive and anxiety symptoms among caregivers was found.…”
Section: Introductionmentioning
confidence: 99%
“…These prevalences are greater than those found in the pre-COVID-19 era (GBD 2017 Diseases and Injuries Collaborators, 2018). Several studies have assessed depression and anxiety using scales involving self-reporting during the pandemic (Ahmad, Rahman, & Agarwal, 2020; Ahn et al, 2020; Ahorsu et al, 2020; Alyami et al, 2020; Amerio et al, 2020; Bachilo, Barylnik, Shuldyakov, Efremov, & Novikov, 2020; Bauer et al, 2020; Bauerle et al, 2020; Chang, Yuan, & Wang, 2020; Chen et al, 2020; Choi, Hui, & Wan, 2020; Civantos et al, 2020; Consolo, Bellini, Bencivenni, Iani, & Checchi, 2020; Fancourt, Steptoe, & Bu, 2020; Filho et al, 2020; Gao et al, 2020; Guo et al, 2020; Hu et al, 2020; Islam, Ferdous, & Potenza, 2020; Jia et al, 2020; Johnson, Ebrahimi, & Hoffart, 2020; Juanjuan et al, 2020; Kantor & Kantor, 2020; Khanna, Honavar, Metla, Bhattacharya, & Maulik, 2020; Killgore, Cloonan, Taylor, & Dailey, 2020; Lai et al, 2020; Lin et al, 2020; Liu, Zhang, Wong, Hyun, & Hahm, 2020a; J. Liu et al, 2020b; Mahendran, Patel, & Sproat, 2020; Mechili et al, 2020; Muñoz-Navarro, Vindel, Schmitz, Cabello, & Fernández-Berrocal, 2020; Naser et al, 2020; Nguyen et al, 2020; Olaseni, Akinsola, Agberotimi, & Oguntayo, 2020; Pieh, Budimir, & Probst, 2020; Qian et al, 2020; Que et al, 2020; Saddik, Hussein, Albanna, et al, 2020a; Saddik, Hussein, Sharif-Askari, et al, 2020b; Salman, Asif, et al, 2020a; Salman, Raza, et al, 2020b; Shi et al, 2020; Sigdel et al, 2020; Solomou & Constantinidou, 2020; Stickley, Matsubayashi, Sueki, & Ueda, 2020; Stojanov et al, 2020; Sun, Goldberg, Lin, Qiao, & Operario, 2020; Tang et al, 2020; Temsah et al, 2020; Ueda, Stickley, Sueki, & Matsubayashi, 2020; Wang et al, 2020; Weilenmann et al, 2020; Xiao et al, 2020; Yamamoto, Uchiumi, Suzuki, Yoshimoto, & Murillo-Rodriguez, 2020; Zhang et al, 2020; Zhao, Peng, Liu, & Ouyang, 2020a; R. Zhao et al, 2020b; Zhou et al, 2020…”
Section: Introductionmentioning
confidence: 99%
“… 16 From the perspective of children requiring long-term kidney replacement therapy (dialysis or kidney transplantation), examples of resource dependency include increased difficulties in accessing medical care and travelling to hospitals for regular kidney function tests, drug concentration monitoring at specialised clinics and acquisition of medical supplies such as peritoneal dialysis fluids and equipment. 17 In a February 2020 Chinese survey of caretakers of children requiring long-term kidney replacement therapy in the midst of the pandemic, these resource-dependent factors were thought by nearly 80% of participants to negatively affect their children’s treatment, with one-third perceiving the effect as severe or extremely severe. 17 EPDWG centre implementation rates of COVID-19 countermeasures, when regarded as changes of ‘institutional behavior’, thus reflected the ability of drivers at each centre to overcome local resource dependency.…”
Section: Discussionmentioning
confidence: 99%
“… 17 In a February 2020 Chinese survey of caretakers of children requiring long-term kidney replacement therapy in the midst of the pandemic, these resource-dependent factors were thought by nearly 80% of participants to negatively affect their children’s treatment, with one-third perceiving the effect as severe or extremely severe. 17 EPDWG centre implementation rates of COVID-19 countermeasures, when regarded as changes of ‘institutional behavior’, thus reflected the ability of drivers at each centre to overcome local resource dependency. These changes, motivated by local perception of growing global medical need, led to diverse local rules and heterogeneous responses.…”
Section: Discussionmentioning
confidence: 99%